Peningkatan Pemasaran Produk Pertanian Berbasis Kewirausahaan di SMA Mayjen Sutoyo Medan - Sinaga, Reflianta; Lubis, Anita Rizky; Sinaga, Anggiat; Purba, Suwandy; Ginting, Nelva; Budiman, Indra (JPM: Jurnal Pengabdian Masyarakat, 2024)
Marketing of agricultural products is done conventionally. However, along with technological advances, conventional marketing is gradually shifting to marketing through online media. Therefore, the millennial generation needs an early understanding of digital media to market agricultural products. Education, training and entrepreneurship conducted by farmers can improve the quality of business management in the optimal agricultural input subsystem. Students at Major General Sutoyo High School who will become future millennial farmers are the hope for developing young agricultural entrepreneurship. This is because farmers are older and not used to using digital technology. The purpose of the community service is to introduce digital marketing in agricultural products to the students of SMA Mayjen Sutoto because they have great potential but a weak bargaining position. Digital marketing is a business that markets products and services to consumers through digital media connected to the internet. The method of this activity is survey, socialization, training to farmers how to manage business in the agricultural input subsystem. The results of this community service are community empowerment activities in managing agricultural product marketing carried out at SMA Mayjen Sutoyo which can be used in good business management (becoming an agricultural business entrepreneur). The enthusiasm given by SMA Mayjen Sutoyo students for this activity is very good, and their enthusiasm is high to take part in coaching, agricultural product marketing techniques and how to use digital marketing in managing an effective agricultural product business.